Trion fine structure and coupled spin–valley dynamics in monolayer tungsten disulfide - Gerd Plechinger (Nature Portfolio, 2016)
Monolayer transition metal dichalcogenides are promising materials for valleytronics applications. Here, the authors study WS2samples using photoluminescence spectroscopy and time-resolved Kerr-rotation measurements at low temperatures, gaining insight into the valley dynamics of excitons.